Crowdfunding: Financing ventures in the digital era - REDDY, Srinivas K. (Institutional Knowledge at Singapore Management University, 2017)
Over the past few years, digital platforms have emerged as a new way to disrupt industries. These platforms not only connect riders and drivers, like Uber, or hosts and guests, like Airbnb, but also ventures and funders. Crowdfunding platforms like Lendingclub or Kickstarter have gained widespread visibility and acceptance in recent years. Crowdfunding was virtually non-existent until 2010 but has been growing exponentially since 2010. In 2015, the volume rose to US$34.4 billion, slightly surpassing the venture capitalist industry and is expected to continue growing quickly.